2015
DOI: 10.1101/cshperspect.a023036
|View full text |Cite
|
Sign up to set email alerts
|

The Function of TrophomiRs and Other MicroRNAs in the Human Placenta

Abstract: In eutherian organisms, the placenta interfaces the fetal and maternal environments. Located at the placental villous surface, in direct contact with maternal blood, is the trophoblast layer, which mediates the crucial maternal-fetal exchange of gases, nutrients, and waste products, produces hormones that support the pregnancy, and provides immunologic defense. Discovery of microRNAs (miRNAs) and their role in development, differentiation, and homeostatic resilience has increased our understanding of genomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 176 publications
(204 reference statements)
2
57
0
3
Order By: Relevance
“…In the present work we did not pursue the exact distribution of C19MC miRNA among extracellular vesicles or in a protein-bound form in the plasma, as demonstrated previously [11,21,31,3739]. Nonetheless, we confirmed the rising levels of C19MC miRNA in exosomes early in pregnancy.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the present work we did not pursue the exact distribution of C19MC miRNA among extracellular vesicles or in a protein-bound form in the plasma, as demonstrated previously [11,21,31,3739]. Nonetheless, we confirmed the rising levels of C19MC miRNA in exosomes early in pregnancy.…”
Section: Discussionsupporting
confidence: 67%
“…Members of this cluster are expressed at a very low level in extravillous trophoblast relative to non-invasive villous trophoblast, and over-expression of C19MC miRNA attenuates migration of extravillous trophoblasts [19]. Furthermore, we found that primary human villous trophoblasts are resistant to infection by diverse DNA and RNA viruses, and this effect could be conferred to other, non-placental cell types by transfecting them with C19MC miRNA, or exposing them to exosomes that contained C19MC miRNA [20,21]. This effect is specific to viruses, as C19MC miRNAs have no effect on infection by intracellular bacteria or protozoa [22].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that cultured primary human trophoblasts (PHTs) are highly resistant to infection by diverse and unrelated viruses and that conditioned PHT culture medium confers resistance to viral infections in nonplacental recipient cells (18). Of importance, we found that C19MC miRNAs are packaged within PHT‐derived exosomes and are released to the extracellular medium where they confer viral resistance to recipient cells by inducing autophagy (18, 19).…”
mentioning
confidence: 99%
“…These biomolecules may affect maternal and fetal tissues, including potential suppression of a maternal immune response against the developing fetus and trophoblast cell migration (24,25). They may also serve as useful biomarkers of pregnancy-related diseases, such as preeclampsia, and fetal trisomy 21 (26 -30).…”
Section: Humanmentioning
confidence: 99%